COMPARISON OF ISCHEMIC COMPRESSION AND PASSIVE STRETCHING FOR TREATMENT OF MYOFASCIAL TRIGGER POINT IN UPPER TRAPEZIUS MUSCLE AMONG DISTRICT JAIL SURVIVORS FAISALABAD - Manzoor, Sidra; Obaid, Summaiyah; Afzal, Farjad; Kousar, Raheela; Azhar, Aroosa; hamna, Mehak; Gilani, Zahra (Annals of Allied Health Sciences, 2017)
Objective: To determine the effectiveness of Ischemic Compression and Passive Stretching for the treatment of Myofascial trigger point in the Upper Trapezius muscle. Methods: Fifty four female jail survivors were recruited for the study. Subjects were healthy individuals, diagnosed with active Myofascial trigger point in the upper trapezius muscle following palpation criteria given by Travell & Simons. Subjects were randomly placed into two groups: Group 1, which received Ischemic compression treatment for Myofascial trigger point; Group 2 received Passive Stretching for Myofascial trigger point. The data was recorded at baseline data, and after one week of intervention. Outcome measures were active range of motion of cervical (measured with Goniometer), pain (measured with Visual analogue scale) and ADLs limitation (measured by using Neck Disability index). Results: There were 27 patients in Group 1 and 27 patients Group 2. Base line VAS score of group 1 was 7.56 while group 2 was 7.30. Base line NDI score of group 1 was 66.67 while group 2 was 63.56. Analysis of baseline data regarding VAS, NDI and cervical ROM showed that there was no significant difference between groups at baseline. After 1 week of treatment VAS score in group 1 decreased to 4.37 while in group 2 it decreased to 3.78. After 1 week of treatment NDI score in group 1 decreased to 32.81 while in group 2 it decreased to 33.63. Cervical ROM was increased in both groups in all planes. Within group analysis showed significant differences in both groups on all three outcome measures. Between group analysis showed no significant differences between groups (P>0.05). Conclusion: Both Ischemic compression and Passive Stretching techniques are effective in the treatment of Myofascial trigger point of trapezius muscle.